2024 update on meningococcal vaccination recommendations for children and adults - Ernest Kuchar; Hanna Czajka; Ewelina Gowin; Maria Katarzyna Borszewska-Kornacka; Aneta Nitsch-Osuch; Anna Skoczyńska; Leszek Szenborn; August Wrotek; Jacek Wysocki; Agnieszka Mastalerz-Migas; Jarosław Peregud-Pogorzelski; Teresa Jackowska (Pediatria Polska)
The best protection against invasive infections caused by meningococcus (Neisseria meningitidis), which can lead to death or permanent disability, is immunization. Its effectiveness has been demonstrated in many countries that have introduced it into national immunization programmes. After 2 years, there was a need to update the Polish recommendations issued in 2022. The epidemiological data have been updated. Complications of invasive meningococcal disease, recommendations for administering booster doses and the management of an epidemiological outbreak have been added to the recommendations. In Poland, meningococcal vaccination has been recommended in the National Immunization Programme for many years, including for 2024, but is not reimbursed. Insufficient public awareness of the risks of meningococcal infections, multiple vaccinations in the first year of a child’s life, involving a large cumulative number of injections, and the cost of the vaccines are other barriers to their acceptance and performance, especially in the youngest children. This publication provides updated management recommendations for physicians implementing meningococcal vaccination in children and adults. This is the result of the work of the expert group established in 2022 under the auspices of the National Consultants in Pediatrics and Family Medicine, who met again in 2024. We recommend starting meningococcal vaccination in the first six months of life with administration of both MenB and MenACWY vaccines at one visit (just after 8 weeks of life), vaccination against MenACWY and MenB of adolescents and young adults – especially those starting college, planning to live in boarding schools or dormitories, or work in the uniformed services, nurseries, kindergartens, or in childcare or health care facilities, or traveling abroad – and use of booster doses of MenB and MenACWY vaccines in patients at high risk of contracting invasive meningococcal disease over the age of 10. We recommend the prophylactic administration of paracetamol to every child under 2 years of age undergoing immunization against MenB, and a proactive vaccination approach. We advocate for the introduction of free-of-charge vaccination for patients from risk groups, urgent action to allow reimbursement of meningococcal vaccines, and the development of regulations for managing meningococcal outbreaks.